Common APOC3 variants are associated with circulating ApoC-III and VLDL cholesterol but not with total apolipoprotein B and coronary artery disease. (October 2020) - Silbernagel, Günther; Scharnagl, Hubert; Kleber, Marcus E.; Hoffmann, Michael M.; Delgado, Graciela; Stojakovic, Tatjana; Gary, Thomas; Zeng, Lingyao; Ritsch, Andreas; Zewinger, Stephen; Speer, Thimoteus; Schunkert, Heribert; et al.
Abstract: Background and aims: Very rare loss-of-function mutations in the apolipoprotein C3 ( APOC3 ) gene have been associated with low circulating apoC-III, low triglycerides, and reduced cardiovascular risk. We aimed to analyze the impact of common APOC3 variants on key parameters of lipid metabolism and coronary artery disease in the largest sample so far. Methods: Common variants in APOC3 were tested for associations with circulating apoC-III, lipids, and apolipoprotein B (apoB) in 3041 participants of the LUdwigshafen RIsk and Cardiovascular health study (LURIC). These variants were then tested for associations with coronary artery disease in a meta-analysis comprising up to 332, 389 participants of the CARDIOGRAMplusC4D consortium and the UK Biobank. Results: The mean (standard deviation) apoC-III concentration was 14.6 (5.1) mg/dl. Seven common variants in APOC3 ( rs734104, rs4520, rs5142, rs5141, rs5130, rs5128, and rs4225 ) were associated with circulating apoC-III (all p  < 0.05). The alleles that modestly raised apoC-III were also associated with markedly higher total triglycerides and very low density lipoprotein (VLDL) triglycerides and cholesterol (all p  < 0.05), but not with low density lipoprotein (LDL) cholesterol and total apoB (all p  > 0.05). These variants were not associated with coronary artery disease in the CARDIOGRAMplusC4D consortium and the UK Biobank (all p  > 0.1). Conclusions: Modest, genetically caused elevations of apoC-III are associated with a marked increase of triglyceride-rich lipoproteins but not with an increase of LDL cholesterol, total apoB, and coronary artery disease. Whether effective inhibition of apoC-III production with antisense oligomers will be instrumental to reduce cardiovascular risk remains to be demonstrated. Graphical abstract: Image 1 Highlights: Common apolipoprotein C3 ( APOC3 ) variants are associated with modest alterations of circulating apoC-III. Common apoC-III raising alleles are associated with increased triglycerides, very low density lipoprotein (VLDL) triglycerides, and VLDL cholesterol. Common apoC-III raising alleles are not associated with increased total apolipoprotein B and low density lipoprotein (LDL) cholesterol. ApoC-III raising alleles are not associated with coronary artery disease in 332, 389 participants of the CARDIOGRAMplusC4D consortium and the UK Biobank.